Prospective evaluation of hypogonadism in male metastatic renal cell carcinoma patients treated with targeted therapies. Issue 3 (4th May 2019) - Bastin, Julie; Werbrouck, Emilie; Verbiest, Annelies; Punie, Kevin; Bechter, Oliver; Woei-A-Jin, Feng Jung; Wolter, Pascal; Wildiers, Hans; Lerut, Evelyne; Dumez, Herlinde; Decallonne, Brigitte; Clement, Paul; et al.
Abstract: Objectives : To study the prevalence of hypogonadism in male patients with metastatic renal cell carcinoma (mRCC) starting with targeted therapies and the impact of the vascular endothelial growth factor receptor tyrosine kinase inhibitors (VEGFR-TKIs) sunitinib and pazopanib on the luteinizing hormone (LH)/testosterone (TT)-axis. Methods : Male mRCC patients starting with targeted therapies were prospectively included in this study. TT- and LH-levels were sampled at start as well as during systemic therapy. Endpoints of the study were gonadal status (TT- and LH-levels) at start of targeted therapy and TT- and LH-evolution during targeted therapy. Results : Sixty-three patients were included in this study. At start of targeted therapy, 30% of patients were eugonadal and 48% had secondary hypogonadism. Decreased TT- and increased LH-levels were associated with inflammatory state and poor prognosis. During sunitinib therapy, TT-levels decreased with 32% ( p = 0.004) and LH-levels with 14% ( p = 0.03). TT-levels were 13% lower ( p = 0.007) and LH-levels 15% lower ( p = 0.004) on day 28 compared to day 1. In four patients, a dramatic TT decrease was observed shortly after starting sunitinib. In patients treated with pazopanib, no impact on TT- or LH-levels was observed. Conclusion : Hypogonadism is a frequent finding in male mRCC-patients at start of targeted therapies. In contrast to pazopanib, during sunitinib therapy, TT- and LH-levels tend to decrease, leading to an increased incidence of secondary hypogonadism.